Development of TP53 mutations over the course of therapy for acute myeloid leukemia. Issue 11 (19th August 2021) - Alwash, Yasmin; Khoury, Joseph D.; Tashakori, Mehrnoosh; Kanagal‐Shamanna, Rashmi; Daver, Naval; Ravandi, Farhad; Kadia, Tapan M.; Konopleva, Marina; Dinardo, Courtney D.; Issa, Ghayas C.; Loghavi, Sanam; Takahashi, Koichi; et al.
Abstract: TP53 mutations in acute myeloid leukemia (AML) are associated with resistance to standard treatments and dismal outcomes. The incidence and prognostic impact of the emergence of newly detectable TP53 mutations over the course of AML therapy has not been well described. We retrospectively analyzed 200 patients with newly diagnosed TP53 wild type AML who relapsed after or were refractory to frontline therapy. Twenty‐nine patients (15%) developed a newly detectable TP53 mutation in the context of relapsed/refractory disease. The median variant allelic frequency (VAF) was 15% (range, 1.1%–95.6%). TP53 mutations were more common after intensive therapy versus lower‐intensity therapy (23% vs. 10%, respectively; p  = 0.02) and in patients who had undergone hematopoietic stem cell transplant versus those who had not (36% vs. 12%, respectively; p  = 0.005). Lower TP53 VAF was associated with an increased likelihood of complete remission (CR) or CR with incomplete hematologic recovery (CRi) compared to higher TP53 VAF (CR/CRi rate of 41% for VAF < 20% vs. 13% for VAF ≥ 20%, respectively). The median overall survival (OS) after acquisition of TP53 mutation was 4.6 months, with a 1‐year OS rate of 19%. TP53 VAF at relapse was significantly associated with OS; the median OS of patients with TP53 VAF ≥ 20% was 3.5 months versus 6.1 months for those with TP5 3 VAF < 20% ( p  < 0.05). In summary, new TP53 mutations may be acquired throughout the course of AML therapy. Sequential monitoring for TP53 mutations is likely to be increasingly relevant in the era of emerging TP53‐ targeting therapies for AML.